Exploring the level of zakat payment awareness among staff at Pejabat Agama Islam (PAID) Daerah Temerloh - Abdul Moin, Nur Asyiqin; Nik Mohd Zainordin, Nik Mohamad Shamim; Musa, Muhammad Fadhli (Journal of Islamic, Social, Economics and Development, 2025)
Every Muslim is obligated to fulfil the fourth pillar of Islam, which is paying zakat, as it plays a vital role in promoting social and economic well-being. However, the level of awareness regarding the importance of paying zakat among Muslims remains relatively low, despite it being a fundamental pillar of the Islamic economic system. This lack of awareness and understanding of zakat knowledge often leads to some individuals failing to fulfil their religious obligation as Muslims. The aim of this study is to assess the level of awareness about paying zakat among the staff of PAID Temerloh and to identify the factors influencing their sensitivity toward fulfilling this obligation. The study employs a quantitative methodology, utilizing Krejcie and Morgan's formula (1970) to determine the sample size from a population of 30 staff members at PAID Temerloh. Data was collected through Google Forms and distributed to 28 staff members selected as the sample. The analysis revealed that while the staff at PAID Temerloh generally have a good understanding of zakat, their awareness of the importance of zakat knowledge remains insufficient. The findings indicate that although almost all staff members are aware of the obligation to pay zakat, there are still gaps in their understanding of how to properly implement it. This study concludes that zakat authorities need to intensify their efforts in promoting the importance of zakat obligations. By doing so, the collection of zakat funds can be increased annually, ultimately contributing to the broader social and economic goals of the Muslim community.